I'm learning numbers = - Smith, Mickenzie; Bell, Valerie (Editor at Flowerpot Press); Flowerpot Press (Franklin, TN : Flowerpot Press, 2016)
"Cuddle up with your little one and this adorable early learning book from Flowerpot Press, and soon you'll hear your little one saying "I'm learning numbers.""--
Cover title.
On board pages.
Keywords: Counting -- Juvenile literature; Board books; Counting; Spanish language materials; Spanish language materials -- Bilingual; Calcul -- Ouvrages pour la jeunesse; Livres tout carton; board books; Board books; Counting; Contar (Enumerar); Juvenile works